Comparative effects of methanol leaf extract of Moringa oleifera and ascorbic acid on haematological and histopathological changes induced by subchronic lead toxicity in male wistar rats - Abubakar Usman; Mohammed Umaru Kawu; Muftau Shittu; Ahmadu Saleh; Kelvin Olutimilehin Jolayemi; Nuraddeen Bello Ibrahim; Joshua Seyi Oyetunde; Magdalene Ogbonneya Okoronkwo (Elsevier, 2022)
This work was aimed at comparing the effects of methanol leaf extract of Moringa oleifera (MLEMO) and ascorbic acid (AA) on haematological changes induced by subchronic lead (Pb) toxicity in male Wistar rats. Thirty-six adult male Wistar rats were randomly grouped into 6 rats per group. Group I received distilled water (2 mL/kg) whereas, groups II, III, IV, V and VI were administered Pb (190 mg/kg), Pb+AA (100 mg/kg), Pb+MLEMO (500 mg/kg), Pb+AA+MLEMO and Pb+AA (50 mg/kg) +MLEMO (250 mg/kg) respectively.  All agents were administered daily by oral gavage for 6 weeks. Blood samples were collected for haematological analysis. Inappetence, facial swelling, emaciation, back arching and nasal discharge were observed only in group II animals. There was significant (P<0.05) decrease in packed cell volume (PCV), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), red blood cell count (RBC) and haemoglobin concentration (Hb) in group II compared to other groups. The leucocyte counts were higher (P<0.05) in group II compared to group V. However, platelet counts were lower (P<0.001) in group II compared to group V. Results from this study, showed that co-administration of MLEMO (250 mg/kg) and AA (50 mg/kg) exert more ameliorative effects in Pb-induced toxicity in male Wistar rats.